Pengembangan Media Game Edukasi Match Up Untuk Meningkatkan Perkembangan Kognitif Anak Kelompok B di TK Negeri Pembina Mataram - Nova Julianti; Gunawan Gunawan; Baik Nilawati Astini; Nurhasanah Nurhasanah (Indonesian Journal of Elementary and Childhood Education, 2024)
This research aims to develop a valid, practical, and effective educational match-up game media to enhance the cognitive development of group B children. This research employed a Research and Development (R&D) approach using the ADDIE development model. The subjects of this research were 21 group B children. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted using descriptive qualitative methods. The results of the research showed that the media expert's assessment to determine the feasibility of the match-up game for group B obtained a percentage of 77% to 96%, and the material expert's assessment obtained a percentage of 79% to 100%, categorized as very feasible. The results of the practicality test by the group B teacher obtained a percentage of 95%, categorized as very practical. The results of the product trial at the school on group B children to determine the level of effectiveness obtained a percentage of 100%, categorized as very effective. This media can be an alternative for teachers to provide fun and interactive cognitive stimulation. Based on the results of this research, it can be concluded that the educational match-up game is feasible, practical, and effective in enhancing the cognitive development of group B children at TK Negeri Pembina Mataram in the 2023/2024 academic year.